Africa must unite. - Nkrumah, Kwame, 1909-1972. (New York, F.A. Praeger, 1963)
President of Ghana traces the effects of colonialism and warns of the dangers of imperialism in trying to break up Africa into small, weak states.
The African background -- The colonial imprint -- Colonial pattern of economics -- Society under colonialism -- The intellectual vanguard -- Freedom first -- Achieving our sovereignty -- Problems of government -- Bringing unity in Ghana -- Our Ghanan consititution -- The administrative instrument -- Reconstruction and development -- Towards economic independence -- Building socialism in Ghana -- Towards African unity -- Some attempts at unification -- Economic and political integration : Africa's need -- Neo-colonialism -- Africa in world affairs -- Examples of major unions of states -- Continental government for Africa.
Includes bibliographical references.
Keywords: Newly independent states; Africa -- History; Ghana -- History; History